Floating Light Ball Reactor: A Scalable and Flexible Photobioreactor Design for Microalgae Cultivation - Gehring, Timo; Maurer, Patrick; Yildirim, Mutlu; Lierse, Maurice Siegfried; Ickes, Richard (Sustainability & Circularity NOW, 2025)
Bringing microalgae cultivation to industrial large-scale production needs photobioreactor designs suitable for economic scale-up to large volumes. Current designs using sunlight lack around-the-clock cultivation, are location dependent, and, when using artificial lighting, do not possess the ability for economic scale-up due to physical connection of lighting to the photobioreactor or thin structures such as tubes or plates. We present a photobioreactor design where floating light balls are used to bring light into the reactor and therefore allow for a flexible and easy scale-up in three dimensions. The physical separation of light balls and reactor housing allows for the transformation of empty containers into photobioreactors. Using a modular and flexible design with assemblies of light balls, we present the transformation of a metal cylinder and a brewery tank into floating light ball reactors for microalgae cultivation. The diatom Phaeodactylum tricornutum was successfully grown on 22-L and 234-L scale in our reactors up to 0.9 g/L dry biomass. Potential biofilm formation can be flexibly handled by quickly cleaning or replacing the light ball assemblies, while at the same time harvesting the biofilm biomass. Our concept is transferrable to all cultivation and reaction systems where light needs to be brought efficiently into a liquid.
Keywords: Algae technology; Scale-up; Photobioreactor; Floating Light Ball Reactor